The Hunt for the Closed Conformation of the Fruit‐Ripening Enzyme 1‐Aminocyclopropane‐1‐carboxylic Oxidase: A Combined Electron Paramagnetic Resonance and Molecular Dynamics Study. Issue 60 (26th September 2019) - Fournier, Eugénie; Tachon, Sybille; Fowler, Nicholas J.; Gerbaud, Guillaume; Mansuelle, Pascal; Dorlet, Pierre; de Visser, Sam P.; Belle, Valérie; Simaan, A. Jalila; Martinho, Marlène
Abstract: 1‐Aminocyclopropane‐1‐carboxylic oxidase (ACCO) is a non‐heme iron(II)‐containing enzyme involved in the biosynthesis of the phytohormone ethylene, which regulates fruit ripening and flowering in plants. The active conformation of ACCO, and in particular that of the C‐terminal part, remains unclear and open and closed conformations have been proposed. In this work, a combined experimental and computational study to understand the conformation and dynamics of the C‐terminal part is reported. Site‐directed spin‐labeling coupled to electron paramagnetic resonance (SDSL‐EPR) spectroscopy was used. Mutagenesis experiments were performed to generate active enzymes bearing two paramagnetic labels (nitroxide radicals) anchored on cysteine residues, one in the main core and one in the C‐terminal part. Inter‐spin distance distributions were measured by pulsed EPR spectroscopy and compared with the results of molecular dynamics simulations. The results reveal the existence of a flexibility of the C‐terminal part. This flexibility generates several conformations of the C‐terminal part of ACCO that correspond neither to the existing crystal structures nor to the modelled structures. This highly dynamic region of ACCO raises questions on its exact function during enzymatic activity. Abstract : The key is flexibility ! A combined experimental and theoretical study has been performed to unravel the conformation of the C‐terminal part of the fruit‐ripening enzyme 1‐aminocyclopropane‐1‐carboxylic oxidase (ACCO; see figure). The results reveal the existence of a flexibility of the C‐terminal part that generates several conformations in this part of the ACCO enzyme.